2006
DOI: 10.1128/jb.188.3.1081-1088.2006
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulation of Arsenite Oxidation in Agrobacterium tumefaciens

Abstract: Seminal regulatory controls of microbial arsenite [As(III)] oxidation are described in this study. Transposon mutagenesis of Agrobacterium tumefaciens identified genes essential for As(III) oxidation, including those coding for a two-component signal transduction pair. The transposon interrupted a response regulator gene (referred to as aoxR), which encodes an ntrC-like protein and is immediately downstream of a gene (aoxS) encoding a protein with primary structural features found in sensor histidine kinases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 43 publications
3
172
1
4
Order By: Relevance
“…The precisely targeted mutation and complementation experiments in the present study provide definitive evidence that the rpoN gene product is essential for aioBA expression and, hence, As III oxidation. This observation also allows a more definitive understanding of the As III oxidase-negative phenotype of the aioR:: Tn5-B22 mutant described previously (28). Specifically, the Tn5-B22 insertion in the extreme 3= region of aioR in the aioS-aioRaioB-aioA operon likely disrupted the DNA binding component of the regulator AioR and is consistent with AioR participating as a bacterial enhancer binding protein in conjunction with RpoN to facilitate the induction of aioBA.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The precisely targeted mutation and complementation experiments in the present study provide definitive evidence that the rpoN gene product is essential for aioBA expression and, hence, As III oxidation. This observation also allows a more definitive understanding of the As III oxidase-negative phenotype of the aioR:: Tn5-B22 mutant described previously (28). Specifically, the Tn5-B22 insertion in the extreme 3= region of aioR in the aioS-aioRaioB-aioA operon likely disrupted the DNA binding component of the regulator AioR and is consistent with AioR participating as a bacterial enhancer binding protein in conjunction with RpoN to facilitate the induction of aioBA.…”
Section: Discussionmentioning
confidence: 71%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 99%
“…The predicted aminoacid sequences of particular proteins encoded by the AIO cluster exhibit 91-100% identity in the amino-acid sequence to the gene products of arsenite oxidation modules of the facultatively chemolithoautotrophic Rhizobium sp. NT26 (Santini and van den Hoven, 2004), and the heterotrophic strains Agrobacterium tumefaciens strain 5A (Kashyap et al, 2006) and Ochrobactrum tritici SCII24 (Branco et al, 2009). Furthermore, the genetic organization of the plasmid pSinA AIO module (aioSRABcytCmoeA) is identical to that of the arsenite oxidase genes of Rhizobium sp.…”
Section: Arsenic Metabolism and Resistance Gene Islandmentioning
confidence: 99%
“…(Stock et al 2000). Previous studies have revealed that the two-component signal transduction system could regulate arsenite oxidation in bacteria (Kashyap et al 2006). Here under arsenate stress, the two-component sensor histidine kinase (spot 14) was also over-expressed in T. pyriformis.…”
Section: Proteomic Responses To Arsenate Exposurementioning
confidence: 83%